Classical tradition in Mercurio Peruano (1791-1795): readings of an enlightened colonial society on the classics of Greece and Rome - Huidobro Salazar, Maria Gabriela (2021)
Through the identification and review of citations and allusions to works and authors of the Greco-Roman Classical Antiquity in the newspaper Mercurio Peruano (1791-1795), the article starts from an approach given by the history of reading and by Classical Reception Studies, to analyze the says of approaching and levels of reading that the literate society of Peru, at the end of the 18th century, could have developed to enter into  contact and dialogue with classical culture. The study is contextualized through an analysis of the titles of classical works and about the ancient world that could circulate in the literate fields and through the educational system of the colonial world. With this, it shows that the authors and readers of the MercurioPeruano had a multiple, dynamic and complex knowledge of the classical authors and their works, which they approached through direct, indirect and measured readings. In this way, they appropriated them as voices of authority and as principles that produce meaning and identity for the formulation and legitimation of their own local and enlightened discourses, accounting for the validity of ancient classical culture, by then, in the enlightened circuit of the colonial society.